2,6-Dimethoxy-1,4-benzoquinone Inhibits 3T3-L1 Adipocyte Differentiation via Regulation of AMPK and mTORC1 - Son, Hyo Jeong; Jang, Young Jin; Jung, Chang Hwa; Ahn, Jiyun; Ha, Tae Youl (Planta Medica, 2019)
2,6-Dimethoxy-1,4-benzoquinone is a natural phytochemical present in fermented wheat germ. It has been reported to exhibit anti-inflammatory, antitumor, and antibacterial activities. However, the anti-adipogenic effects of 2,6-dimethoxy-1,4-benzoquinone and the mechanisms responsible have not previously been elucidated. Such findings may have ramifications for the treatment of obesity. 2,6-Dimethoxy-1,4-benzoquinone (5 and 7.5 µM) significantly reduced the expression of various adipogenic transcription factors, including peroxisome proliferator-activated receptor-γ and CCAAT/enhancer binding protein α as well as adipocyte protein 2 and fatty acid synthase. 2,6-Dimethoxy-1,4-benzoquinone upregulated AMP-dependent protein kinase phosphorylation and inhibited the mature form of sterol regulatory element-binding protein 1c. Notably, 2,6-dimethoxy-1,4-benzoquinone attenuated mammalian target of rapamycin complex 1 activity in 3T3-L1 and mouse embryonic fibroblast cells. These findings highlight a potential role for 2,6-dimethoxy-1,4-benzoquinone in the suppression of adipogenesis. Further studies to determine the anti-obesity effects of 2,6-dimethoxy-1,4-benzoquinone in animal models appear warranted.
Keywords: 2,6-dimethoxy-1,4-benzoquinone (DMBQ); adipogenesis; AMPK; mTORC1; obesity